DAMPAK PROGRAM DISKON DAN PEMBEBASAN BBNKB II TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DI SAMSAT PATI - Sarastanto Aulia Heru Pranoto; Mochamad Arif (JURNAL STIE SEMARANG, 2025)
This study aims to analyze the effect of tax discount programs, the exemption of the second Motor Vehicle Title Transfer Fee (BBNKB II), and tax socialization on the level of taxpayer compliance at the Samsat Office of Pati Regency. The background of this research is based on fluctuations in motor vehicle tax (PKB) and title transfer fee (BBNKB) revenues over the past five years, which indicate that taxpayer compliance remains relatively low. The Central Java Provincial Government has implemented several incentive policies such as tax discount programs, BBNKB II exemptions, and extensive tax socialization campaigns to improve public awareness and compliance. This research employed a quantitative approach with an associative method. The population consisted of 216,643 registered motor vehicle taxpayers in Pati Regency. Using the Slovin formula, a sample of 100 respondents was selected through accidental sampling. Primary data were collected through questionnaires distributed to taxpayers, while secondary data were obtained from documentation at the Samsat Office. Data were analyzed using multiple linear regression analysis, with additional tests for validity, reliability, t-test, F-test, and coefficient of determination (R²) using the SPSS application. The results showed that: (1) the tax discount program had a positive and significant effect on taxpayer compliance; (2) the BBNKB II exemption had a positive but not significant effect on taxpayer compliance; and (3) tax socialization had a positive and significant effect on taxpayer compliance at the Pati Regency Samsat Office. Simultaneously, the three independent variables significantly influenced taxpayer compliance. These findings indicate that fiscal incentive policies and effective tax socialization play an important role in improving taxpayer compliance. Therefore, it is recommended that the government continue to enhance tax discount programs and strengthen socialization strategies through innovative public communication and efficient service delivery to further increase taxpayer discipline.